Agreement between Corneal Thickness Measurements Using Pentacam Scheimpflug Camera, Noncontact Specular Microscopy, and Ultrasonographic Pachymetry in Diabetic Patients. (1st February 2017) - Altay, Yeşim; Balta, Ozgur; Demirok, Gülizar; Burcu, Ayse; Balta, Oyku Bezen; Ornek, Firdevs
ABSTRACT: Purpose : To evaluate the agreement of corneal thickness (CT) measurements obtained by the Pentacam Scheimpflug camera, noncontact specular microscopy (SM), and ultrasonographic pachymetry (UP) in diabetic (DM) patients; and whether duration of diabetes and level of Hb A1c affect the agreement. Materials and Methods : The CT was measured in 127 patients with DM, and 137 age and sex-matched healthy controls sequentially by Pentacam, SM, and UP. Also diabetic subjects were subdivided according to duration of diabetes and Hb A1c levels. Pearson correlation analysis, linear regression analysis, and Bland–Altman plots were used for examination of agreement. Results : We found an excellent and statistically significant correlation of CT measurements between Pentacam–SM ( R 2 = 0.768; R 2 = 0.855), Pentacam–UP ( R 2 = 0.546; R 2 = 0.652), and SM–UP ( R 2 = 0.759; R 2 = 0.797) in diabetic and control groups, respectively. We performed further comparisons of the pair of instruments using the Bland–Altman analysis, and the mean difference between pair of methods was much smaller for SM–UP pair (−4.20 ± 9.79 in diabetic, and −4.58 ± 8.08 in control group). The group having Hb A1c level less than 7.5% showed the best agreement between SM–UP pair as in the control group. Whereas Pentacam–UP showed the best agreement in the group having Hb A1c level ≥7.5%. The best agreement was between Pentacam–UP in 0–4 year group, and between Pentacam-SM in 5–9 year and ≥10 year groups. Conclusion : SM–UP pair showed a higher agreement in diabetic patients. According to subgroup analyses, Hb A1c level, rather than the duration of diabetes, may determine the agreement of these pachymetry devices. But the difference in CT measurements between devices can still influence clinical diagnosis and treatment. Therefore, these methods are not completely interchangeable.